Capnography as a tool for triaging and diagnosis of diabetic ketoacidosis in the emergency department: A prospective observational study - Suhrith Bhattaram; Varsha Sambhaji Shinde; Princy Panthoi Khumujam; Anjeeth Puthoor Anilkumar; Dhruva Kumar Reddy (Turkish Journal of Emergency Medicine)
OBJECTIVES: The cornerstone of management of acidosis in a patient with diabetic ketoacidosis (DKA) has traditionally been carried out by blood gas analysis, which is expensive and associated with significant risk. It is against this background that the correlation between end-tidal carbon dioxide (EtCO2), blood pH, and EtCO2 bicarbonate levels was analyzed. The predictive value of EtCO2 was also analyzed in the diagnosis of DKA. Finally, we aimed to determine the value of EtCO2 as a screening test for the exclusion of DKA. MATERIALS AND METHODS: This was a prospective cohort study carried out in the emergency department of a tertiary care teaching hospital from September 2020 to September 2021. Patients with suspected DKA underwent simultaneous blood gas collection and EtCO2 analysis. RESULTS: A total of 123 patients with blood sugar levels >250 mg/dl and moderate-to-large (≥2+) urine ketones were studied. A cut-off value of EtCO2 ≤24 was determined to rule in DKA with a sensitivity of 93.02% and specificity of 91.9%. EtCO2 >26 could effectively rule out the diagnosis of DKA with sensitivity of 98.8% and specificity of 75.7%. A significant linear correlation between pH and EtCO2 (P < 0.0001, r = 0.82) and HCO3 and EtCO2 (r = 0.896, P < 0.0001) was found. CONCLUSIONS: EtCO2 values ≤24 can accurately identify patients with DKA in the presence of elevated blood sugar and urinary ketones and must be considered a valuable addition to the diagnostic criteria. EtCO2 values >26 can be an effective triaging tool for ruling our DKA. A significant linear correlation between pH and EtCO2 and pH and HCO3 was observed. EtCO2 can be considered a surrogate marker for the degree of response to the treatment in DKA.